Reviewing time intervals from onset of the symptoms to thrombolytic therapy in patients with ST segment elevation myocardial infarction (STEMI) - Moeini, Mahin (Medknow Publications Pvt Ltd, 2010)
BACKGROUND: Coronary artery diseases are one of the causes of early death all over the world. In developed countries, ischemic heart disease is responsible for half of the entire mortalities; however in developing countries it is estimated that from 9 million deaths per year, 32 percent are due to coronary artery disease. Acute coronary syndromes are responsible for over 250,000 deaths per year caused by progressive atherosclerotic process which would lead to rupture of the atherosclerotic plaque and establishing thrombosis. This study aimed to determine time intervals between the onset of the heart attack symptoms to thrombolytic therapy in patients with ST segment elevation myocardial infarction (STEMI) in selected hospitals of Isfahan University of Medical Sciences. METHODS: In this study, 180 subjects with first time STEMI were enrolled by categorized random sampling in cardiac care units of four hospitals affiliated to Isfahan University of Medical Sciences during 9 months. Necessary information were collected by asking the patients and reviewing their records. The data included demographic, prehospital and in-hospital data of the patients. RESULTS: The mean duration of time interval from the onset of heart attack symptoms to the first action in order to seek medical care was 01:16’(01:36’) (h:m [SD]), from the symptoms onset to admission in emergency unit was 02:29’(02:00’) and from admission in emergency unit to administration of thrombolytic drug was 01:04’(01:14’). CONCLUSIONS: Time interval between onset of the acute coronary symptoms and seek for medical care and arrival to the emergency unit in this study had a better condition than other studies, but the interval between the emergency admission and thrombolytic therapy was longer than other studies.